Place, belonging, and more-than-human community: a visual study of older lesbians in rural Tasmania. Issue 4 (2nd October 2021) - Grant, Ruby; Walker, Briohny
ABSTRACT: Rural areas have long been represented as unwelcoming to lesbian, gay, bisexual, transgender, and queer (LGBTQ) communities. However, demographic trends show that lesbians are more likely than gay men to live in rural Australia, especially as they age. Despite this, little is known about lesbians' motivations for living in these areas, how they experience rural communities, or what aspects of rural places support positive ageing for this group. Lesbian and feminist geographies highlight how lesbians have often cultivated socio-political links with the natural world. Building on this work, in this article we explore how older lesbians experience place-based belonging in rural communities and the role of more-than-human actors in fostering a sense of home. Through in-depth interviews with 13 women over 55 and participant-produced photography, we identified three overarching themes: (1) More-than-human Community; (2) Gardening as Placemaking and Community Building;(3) Belonging and Acknowledging Risk. In contrast with notions of lesbians as being 'out of place' in rural communities, we argue that belonging is established both through human and more-than-human kinships formed in rural places. By visually representing their lives in rural communities, our participants challenged the invisibility of older lesbians and demonstrated how the rural can offer rich possibilities for multi-species futures.